Spousal Concordance of Physical Frailty in Older Korean Couples - Kang, Suah (Int J Environ Res Public Health, 2020)
Marital status is an important risk factor for physical frailty. However, there are limited data on spousal concordance of physical frailty among married couples. Here, we evaluate the spousal concordance of frailty as defined by the Fried frailty phenotype and specific phenotype components that contribute to this association. Data on 315 married couples (630 individuals) aged between 70 and 84 years were obtained from the Korean Frailty and Aging Cohort Study (KFACS). Multivariate logistic regressions were used for the analysis. After adjusting for covariates (age, body mass index, education, house ownership, comorbidity, cognition, depressive symptoms, cohabitation with adult children for both partners), a husband’s frailty was positively associated with his wife’s frailty (odds ratio (OR) 3.34, 95% confidence interval (CI) 1.04–10.73, p < 0.05), and a wife’s frailty was significantly associated with her husband’s frailty (OR 4.62, 95% CI 1.31–16.33, p < 0.05), indicating a greater effect of the frailty status of the spouse among women than among men. Among the five components of the Fried frailty phenotype, weight loss, slowness, and exhaustion were the main contributing factors to the spousal association for frailty. In conclusion, having a frail spouse is a strong and independent risk factor for frailty among community-living older adults.